Literature Review: The Effect of Spiritual Emotional Freedom Technique Therapy on Patients with Depression - Sucipto Sucipto; Heny Kristanto; Wijayanti Chintya Dhevansa (Indonesian Journal of Global Health Research, 2023)
Depression is a disorder of a person's feelings, emotions and behavior negatively which can make a person feel lost, empty and have no zest for life. To treat depression, you can use Spiritual Emotional Freedom Technique (SEFT) therapy which aims to change feelings, thoughts to become calmer and relaxed. and willingly accept trials. The purpose of this study was to analyze a journal entitled the effect of SEFT therapy on patients with depression. The research design used a literature review with a data collection strategy using inclusion-exclusion in the PICOS format. The search method in this study used the Google Scholar and Semantic Scholar databases by entering the words "SEFT Therapy" OR "Depression". Search articles were limited to inclusion criteria and exclusion criteria. The inclusion criteria in this study were SEFT therapy in depression, the pre-experimental and quasy-experimental research designs, while the exclusion criteria was the management of depression without SEFT therapy. The results of the analysis of this study found that there was an effect before and after the Spiritual Emotional Freedom Technique therapy was carried out in patients with depression. The use of Spiritual Emotional Freedom Technique therapy must be done properly, from the therapeutic steps to the pronunciation of the therapy, because it is very influential in patients with depression.